Breast implant-associated anaplastic large cell lymphoma: a diagnostic challenge - Ana Paula De-Azambuja; Anne Karoline Groth; Juliana Jung; Fabiola Gevert; Samir Kanaan Nabhan (Revista Brasileira de Cirurgia Plástica, 2020)
Breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) is a provisional entity with morphological and immunophenotypic characteristics indistinguishable from ALK-negative anaplastic large cell lymphoma (ALCL). Unlike ALCL, BIA-ALCL arises mainly in association with breast implantation. Diagnostic confirmation of BIA-ALCL can be difficult and associating morphological and pathological hallmarks with flow cytometry and immunohistochemistry can assist in the diagnosis. The objective of this report is to describe a case of BIA-ALCL in which cytological and immunophenotypological analysis using flow cytometry suggested the presence of large CD30-positive cells in the effusion fluid.